Conversion Mechanism of Toxic Hydrogen Cyanide by Magnesium Oxide at High Temperatures - Xiong, Yingying; Wang*, Xuebin; Zhang, Limeng; Hu, Zhongfa; Niu, Yanqing; Tan, Houzhang (Asian Journal of Chemistry, 2015)
Hydrogen cyanide (HCN) is the most important precursor of NOx in coal combustion and is also a high toxic production in coal chemical industry. In the present study, investigations on HCN converting using magnesium oxides was carried out in a fixed bed at 300-1273 K and the original HCN was produced by the pyrolysis of pyridine. Effects of temperature, volume space velocity and initial HCN concentration on HCN conversion were considered. Results showed that temperature was the major factor affecting HCN conversion and it undergoes different conversion mechanism in different temperature scale. With the formation of CO at 723 K, HCN started to decrease and kept a constant value from 873 to 973 K. After 973 K, HCN decreased significantly and CH4 from the pyrolysis of pyridine also decreased, but CO disappeared at 973 K. When temperature was higher than 1123 K, HCN was converted totally. In the isothermal experiments, N2 was detected at 1123 K but not at temperatures lower than 923 K and the nitrogen element in N2 was equal to that in the removal of HCN. It indicated that below 973 K MgO removed HCN by the pathway However, MgO acted as catalyst at above 973 K and HCN was converted to N2 by the reaction